Inhibition of esophageal squamous cell carcinoma progression by MIR210HG and activation of the P53 signaling pathway to promote apoptosis and autophagy - Jianyu Wang; Zhenhu Zhang; Liang Song; Xiangyan Liu; Xiaopeng He (European Journal of Medical Research)
Abstract Background Esophageal squamous cell carcinoma (ESCC) stands among the frequently occurring malignancies. The lack of efficient early detection methods and therapeutic approaches leads to a high mortality rate for ESCC. The long noncoding RNA MIR210HG is strongly related to various malignant tumors. However, its involvement in ESCC remains unexplored. Thus, this investigation aimed to assess the involvement of MIR210HG in ESCC development. Methods The MIR210HG expression was analyzed in numerous tumor types through pan-cancer analysis of The Cancer Genome Atlas(TCGA) database. This research investigated the MIR210HG role in the survival and prognosis of individuals with ESCC. The biological functions of MIR210HG were examined by enrichment analyses, including GO, GSEA, and KEGG. Moreover, immune cell infiltration, tumor microenvironment (TME) characteristics, and immune checkpoint expression levels associated with MIR210HG were explored. To get more insight into the connection between MIR210HG and ESCC, we assessed related gene and protein expression using Western blotting and qRT-PCR. To evaluate the proliferation, invasion, migration, apoptosis, and autophagy of ESCC cells, various techniques were employed, including EdU proliferation tests, monodansylcadaverine (MDC) staining, wound healing assays, cell colony formation, transwell assays, flow cytometry, and an established xenograft mouse model. Results MIR210HG exhibited low expression levels in ESCC. High expression of MIR210HG correlated with a higher survival rate among patients. The elevated expression of MIR210HG hindered the ESCC cell's ability to proliferate, invade, and migrate, both in vivo and in vitro settings. Furthermore, a positive correlation between MIR210HG and the P53 signaling pathway was observed, which could affect autophagy and apoptosis in ESCC cells. Conclusions MIR210HG emerges as a pivotal gene in ESCC, influencing both the immunity and prognosis of patients. Moreover, it may affect autophagy and apoptosis via the P53 signaling pathway. Overall, these outcomes present novel ideas for ESCC treatment.